Impact of the veneering technique and framework material on the failure loads of all-ceramic computer-aided design/computer-aided manufacturing fixed partial dentures - Hinz, Sebastian; Bensel, Tobias; Bömicke, Wolfgang; Henningsen, Anders; Rudolph, Judith; Boeckler, Arne Hellmut Wilhelm Fritjof (Materials, 2022)
Objectives: Zirconia (Y-TZP) ceramics are considered as posterior fixed partial denture (FPD) materials; however, their applications are limited due to chipping. The use of monolithic lithium disilicate (LiDi) glass ceramics in posterior FPDs can be advantageous. This in vitro study aims to compare the loads until failure of posterior Y-TZP-FPDs and LiDi-FPDs before and after aging.